Análise eletro-óptica do ruído de um sensor de imagem em modo logarítimico a temperaturas criogênicas - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Digital cameras became quickly the main image-capturing devices. They not only replaced the film cameras, but also enabled new applications. Among the most important technologies in the design of digital cameras is the use of CMOS image sensors instead of charge-coupled devices (CCD). CMOS technology allows the integration of capture and processing on a single chip, reducing the size, energy and costs. Despite these advantages, CMOS image sensors have an increased noise in some pixel design architectures. The noise deteriorates the image and determines the sensor sensitivity. In this thesis a technique will be developed to quantify the noise in CMOS image sensors, putting aside the main noise sources in low temperatures (cryogenic) and measuring it depending on the brightness. In general, these results are obtained (whether in image sensors or in simple devices) via dedicated commercial equipment that are extremely expensive (about R$ 260.000,00), an example of such equipment would be (E4727A -Advanced Low LoiseAnalyzer), however, this problem can be overcome, in part, using own development systems, which will be one of the objectives of this work, making it possible to analyze using existing equipment in the optical laboratory materials - OptiMa.
Keywords: Sensores de Imagem; Ruído em Dispositivos Eletrônicos; Ruídos em Sensores de Imagem; Modelamento do Ruído em Dispositivos; ENGENHARIAS: ENGENHARIA ELÉTRICA